New Procedure to Maintain Fecal Microbiota in a Dry Matrix Ready to Encapsulate - Aira, Andrea; Rubio, Elisa; Ruiz, Andrea; Vergara, Andrea; Casals-Pascual, Climent; Rico, Verónica; Suñé-Negre, Josep Maria; Soriano, Alex (Frontiers in Cellular and Infection Microbiology, 2022)
Fecal microbiota transplantation (FMT) is one of the recommended treatments for recurrent Clostridioides difficile infection, but endoscopy and available oral formulations still have several limitations in their preparation, storage, and administration. The need of a viable oral formulation which facilitates the implementation of this highly effective therapy in different settings has led us to test the microcrystalline cellulose particles as adsorbent of concentrated filtered fresh feces in comparison to lyophilized feces. This free-flowing material can provide protection to bacteria and results in a dried product able to maintain the viability of the microbiota for a long time. Adsorbate formulation showed a stabilizing effect in gut microbiota, maintaining bacteria viability and preserving its diversity, being a competitive option for lyophilized capsules.